Young adults in the workplace A multisite initiative of substance use prevention programs - Bray, Jeremy W.; Galvin, Deborah M.; Cluff, Laurie A. (RTI Press Publication, 2010)
The Substance Abuse and Mental Health Services Administration funded the multisite Young Adults in the Workplace (YIW) initiative to study the effectiveness of diverse approaches to workplace-based prevention of substance abuse. Six teams adapted evidence-based programs to target young employees and then implemented the programs in retail, restaurant, health care, construction, skilled trade, and transportation industry workplaces. This book describes the programs, the adaptation and implementation processes, and the YIW cross-site evaluation.